Trade Agreements and the Nature of Price Determination - Antràs, Pol; Staiger, Robert W (American Economic Review, 2012)
According to the terms-of-trade theory, negotiations over tariffs alone, coupled with an effective market access preservation rule, can bring governments to the efficiency frontier. In this paper, we show that the nature of international price determination is important for this central result of the terms-of-trade theory. While the received theory assumes that international prices are fully disciplined by aggregate market clearing conditions, we show here that support for “shallow” integration is overturned, and instead a need for “deep” integration is suggested ? wherein direct negotiations occur over both border and behind-the-border policies ? if international prices are determined through bargaining.